Treatment of contents linguistic and grammatical textbooks in series: Hacia el Siglo XXI - Rojas Blanco, Lillyam (2011)
It focuses on the secondary books Series: Hacia el Siglo XXI published by the University ofCosta Rica and the Ministry of Public Education. We analyze the presentation and development of linguistic and grammatical issues in Costa Rica, Spanish, language rules, spelling, vocabulary, morphology, syntax-, student motivation and student, the preparation and presentation of the different practices and exercises. It is emphasized that these texts constitute a valuable and updated to the Costa Rican education.